A simple steady-state inflow model of the neutral and stable atmospheric boundary layer applied to wind turbine wake simulations - M. P. van der Laan; M. Kelly; M. Baungaard; A. Dicholkar; E. L. Hodgson (Wind Energy Science)
Wind turbines are increasing in size and operate more frequently above the atmospheric surface layer, which requires improved inflow models for numerical simulations of turbine interaction. In this work, a steady-state Reynolds-averaged Navier–Stokes (RANS) model of the neutral and stable atmospheric boundary layer (ABL) is introduced. The model incorporates buoyancy in the turbulence closure equations using a prescribed Brunt–Väisälä frequency, does not require a global turbulence length-scale limiter, and is only dependent on two non-dimensional numbers. Assuming a constant temperature gradient over the entire ABL, although a strong assumption, leads to a simple and well-behaved inflow model. RANS wake simulations are performed for shallow and tall ABLs, and the results show good agreement with large-eddy simulations in terms of velocity deficit from a single wind turbine. However, the proposed RANS model underpredicts the magnitude of the velocity deficit of a wind turbine row for the shallow ABL case. In addition, RANS ABL models can suffer from numerical problems when they are applied as a shallow-ABL inflow model to large wind farms due to the low-eddy-viscosity layer above the ABL. The proposed RANS model inherits this issue, and further research is required to solve it.